Molecular characterization of persistent subclinical mastitis-causing Staphylococcus aureus from dairy farms - Gonçalves, Juliano Leonel; Lee, Sarah H. I.; Camargo, Carlos H.; Zanella, Rosemeire Cobo; Silva, Nathália C. C.; Rall, Vera. L. M. [UNESP]; Cue, Roger I.; dos Santos, Marcos V. (Springer Nature, 2023)
The study aimed to evaluate the genetic diversity of Staphylococcus aureus causing subclinical mastitis (SM) isolated from dairy cows and to assess the effect of the infection status (transient vs. persistent) on the milk and component yield. A total of six dairy farms in São Paulo state were used for the selection of cows with SM caused by S. aureus. S. aureus strains (n = 56) obtained from three biweekly aseptic mammary quarter milk samplings (n = 1140 from 95 cows) were subjected to MALDI-TOF MS analysis for species confirmation and further PFGE analysis. Intramammary infections (IMI) caused by S. aureus were categorized as transient (T: when only one out of 3 milk samplings had positive isolation of any pulsotype) or persistent (P: when two (P2) or three (P3) milk samplings had positive isolation of identical pulsotype over the consecutive episodes of SM. The SmaI macrorestriction fragment profiles of 56 S. aureus isolates showed a dominant S. aureus clonal pattern (PFGE type A; n = 50; 89.3%) within and among the herds. The SM-causing S. aureus represented a reduction of quarter milk yield of 26.2% in transient and 54.8% in persistent cases as well as a reduction of total solid yield of 38.1% and 49.4%, respectively, when compared with the healthy control quarters. Overall, the greater chance of S. aureus to be persistent is when a dominant clonal pattern is present in the herd which consequently may be associated with the cause of accentuated milk loss.
Keywords: Chronic infection; Genetic diversity; Milk reduction; PFGE; Staphylococci